2022
DOI: 10.3389/fmicb.2022.1029128
|View full text |Cite
|
Sign up to set email alerts
|

Seminal and vagino-uterine microbiome and their individual and interactive effects on cattle fertility

Abstract: Reproductive failure is a major economical drain on cow-calf operations across the globe. It can occur in both males and females and stem from prenatal and postnatal influences. Therefore, the cattle industry has been making efforts to improve fertility and the pregnancy rate in cattle herds as an attempt to maintain sustainability and profitability of cattle production. Despite the advancements made in genetic selection, nutrition, and the implementation of various reproductive technologies, fertility rates h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 123 publications
0
11
0
Order By: Relevance
“…Compared to the gut microbiota, there is limited information available on the early life female reproductive microbiota in either humans or cattle, making it difficult to make any inferences on whether or how prenatal VTM supplementation-induced changes in the vaginal microbiota of calves would impact reproductive health and fertility later in life. Nevertheless, given the increased appreciation of the role of female reproductive microbiome in defining human (77, 78) and bovine reproductive health and fertility (5), our findings can be interpreted to imply that maternal nutritional factors could influence offspring reproductive tract microbiome.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Compared to the gut microbiota, there is limited information available on the early life female reproductive microbiota in either humans or cattle, making it difficult to make any inferences on whether or how prenatal VTM supplementation-induced changes in the vaginal microbiota of calves would impact reproductive health and fertility later in life. Nevertheless, given the increased appreciation of the role of female reproductive microbiome in defining human (77, 78) and bovine reproductive health and fertility (5), our findings can be interpreted to imply that maternal nutritional factors could influence offspring reproductive tract microbiome.…”
Section: Discussionmentioning
confidence: 84%
“…The microbial communities residing within the respiratory (3), gastrointestinal (4), and reproductive tracts (5, 6), are vital to cattle health and productivity as they mediate nutrient metabolism, modulate the immune system, and provide colonization resistance against pathogens when they maintain their symbiotic relationship with the host. In addition to the microbiota present in these three anatomical sites, recent developments highlight that commensal microbiota associated with the oculus (7), hoof (8), and liver (912) may mediate bovine ocular, hoof, and liver health.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we observed changes in the vaginal microbiota characterized by the increase in the phyla Actinobacteriota and decrease of Proteobacteria and Fusobacteria of RES heifers. These three phyla are important members of the microbial communities in the vagina and uterus of cattle, and their presence has been reported in fetal samples (Luecke et al, 2022;Messman and Lemley, 2023). These phyla are also dominant phyla correlated with gut, reproductive, and respiratory tract-associated microbiota of newborn calves (Luecke et al, 2023).…”
Section: Discussionmentioning
confidence: 94%
“…The third limitation was associated with freezing the semen samples prior to the culturing, which might have limited the recovery of certain bacterial species. Despite these limitations, there are several strengths in our study compared to the other studies on the bull seminal microbiota published so far ( 58 ). The semen samples used in our study were from the same bulls collected at three different time points, which represent different bull growth and developmental stages, and from three full spermatogenic cycles, as well as pre- and postbreeding stages, providing novel and important information on how the seminal microbial community changes with age and is influenced by breeding activity.…”
Section: Discussionmentioning
confidence: 97%